2020
DOI: 10.1021/acs.jced.0c00791
|View full text |Cite
|
Sign up to set email alerts
|

Isobaric Vapor–Liquid Equilibria for Binary Mixtures of Gamma-Valerolactone + Toluene

Abstract: Because of the outstanding physical and chemical properties of biomassoriginated γ-valerolactone (GVL), it has been characterized as a promising alternative platform molecule, which can be utilized as an oxygenate in fuels and green solvents. Herein, the isobaric vapor−liquid equilibrium (VLE) of GVL and toluene, which was selected as a representative of aromatic hydrocarbons, was investigated at p = 101.3 and 50.7 kPa. The experimental data were correlated with Wilson, NRTL, and UNIQUAC activity coefficient m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Recently, some works in the literature covered thermophysical properties for pure GVL and its mixtures, such as vapor pressure, , density, ,, viscosity, refractive index, ,, excess enthalpy, , heat capacity, ,, and thermal diffusivity . Also, the vapor–liquid equilibria of binary mixtures of GVL + water, , toluene, acetic acid, acetone and ethyl acetate, and short chain alcohols were investigated, and no azeotropes were observed. For the liquid–liquid equilibria (LLE), binary mixture data are available for GVL and several hydrocarbons. , In the past few years, our research group investigated LLE of model systems for studying the solvent extraction as a purifying step in the Fischer–Tropsch diesel process.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some works in the literature covered thermophysical properties for pure GVL and its mixtures, such as vapor pressure, , density, ,, viscosity, refractive index, ,, excess enthalpy, , heat capacity, ,, and thermal diffusivity . Also, the vapor–liquid equilibria of binary mixtures of GVL + water, , toluene, acetic acid, acetone and ethyl acetate, and short chain alcohols were investigated, and no azeotropes were observed. For the liquid–liquid equilibria (LLE), binary mixture data are available for GVL and several hydrocarbons. , In the past few years, our research group investigated LLE of model systems for studying the solvent extraction as a purifying step in the Fischer–Tropsch diesel process.…”
Section: Introductionmentioning
confidence: 99%
“…For the K -value error models, it is evident that only minor errors of K 1 appeared, while for K 2 , the errors were between 0.07 and 3.1 and between 0.1 and 3.3 at atmospheric and reduced pressures, respectively. Such greater errors in K 2 and smaller in K 1 can be expected when the mixture shows higher relative volatilities . The figures of the relative volatilities and the K -value errors are introduced in the Supporting Information (Figures S5–S10).…”
Section: Resultsmentioning
confidence: 99%
“…Such greater errors in K 2 and smaller in K 1 can be expected when the mixture shows higher relative volatilities. 45 The figures of the relative volatilities and the Kvalue errors are introduced in the Supporting Information (Figures S5−S10).…”
Section: = −mentioning
confidence: 99%
“…Among them, its stability in contact with air, relatively low vapor pressure and high boiling point, smell for recognition, and miscibility in water assure GVL biodegradability and safety in storage and transportation. ,, Other studies also show encouraging results for its use as a solvent. For instance, the absence of an azeotrope in the vapor–liquid equilibrium (VLE) data of binary mixtures of GVL and water, , toluene, formic acid, acetone and ethyl acetate, and short-chain alcohols may not demand a complex operation for its recovery and reuse in a certain process. Regarding the liquid–liquid equilibrium (LLE), it was shown that miscibility between GVL and a hydrocarbon in binary mixtures reduces as the alkyl chain length increases. , Moreover, Klajmon et al investigated ternary systems with GVL + toluene + hydrocarbon ( n -heptane, or n -decane, or n -dodecane, or cyclohexane), these components being of interest in applications related to fuels and to the Fischer–Tropsch (FT) synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…8,10,11 Other studies also show encouraging results for its use as a solvent. For instance, the absence of an azeotrope in the vapor−liquid equilibrium (VLE) data of binary mixtures of GVL and water, 12,13 toluene, 14 formic acid, 15 acetone and ethyl acetate, 16 and short-chain alcohols 17 may not demand a complex operation for its recovery and reuse in a certain process. Regarding the liquid−liquid equilibrium (LLE), it was shown that miscibility between GVL and a hydrocarbon in binary mixtures reduces as the alkyl chain length increases.…”
Section: Introductionmentioning
confidence: 99%